Prospect refugia: constructing climate change resilient ecosystems - Ryan, James (Kansas State University, 2021)
“Prospect Refugia: Constructing Climate Change Resistant Ecosystems” is a landscape design playbook developed to inform and prepare landscape architects and land planners about the changing climatic threats facing the world and how to mitigate ecosystem degradation caused by climatic forces. The ecosystem construction playbook acknowledges global and national trends while proposing regional and site-specific design strategies. Regional and site-specific focuses help maximize the protection of native high-taxa biodiversity and high-risk species from extinction and extirpation due to climate change. While the design of refugia is the focus of this document, connectivity of individual refugium and remnant habitats is paramount to the success of a greater refugia system. Borrowing principles from Grose (2017), Forman & Godron (1981), and Forman (1995; 2008) my work builds upon existing foundations of landscape connectivity and novel ecosystem construction for climate change resilience. The development of region-specific climate refugia allows for shifting native species associations and adaptive ecosystem continuities to mitigate rapid climate change across the Midwest, the United States, and the world at large.
Keywords: Climate change; Refugia; Ecosystem migration; Environmental planning; Landscape architecture